다천체 분광 관측을 위한 Robotic Fiber Positioner 및 Path Planning 알고리즘 개발 - 임현호; 김재우; 황호성; 홍성욱; 이종철; 최영만 (한국정밀공학회지, 2025)
A robotic focal plane system using robotic fiber positioners enables multi-object spectroscopy for hundreds to thousands ofgalaxies by utilizing a dense array of positioners that are closely packed at the focal plane of a telescope. While this densearrangement increases the number of observations, it also introduces the potential for collisions between adjacentpositioners. A fiber positioner is designed similarly to a SCARA robot. It is driven by two series of BLDC motors. Eachpositioner is manufactured with an outer diameter of 16 mm. It operates within an annular workspace with an outerdiameter of 33.6 mm and an inner diameter of 12.8 mm. As these positioners are arranged with a spacing of 16.8 mm,target assignment and motion planning are critical to avoid collisions caused by overlapping workspaces. To address this,we proposed an optimized step choice algorithm using a motion planning method based on optimization with the sequentialquadratic programming algorithm. Simulation results demonstrated that paths for all positioners within a tile weresuccessfully generated with a success rate of up to 93.75% across 80 tiles.
Keywords: SCARA robot; High-precision positioning; Fiber positioner; Swarm bot; Path planning; Collision avoidance; 스카라 로봇; 고정밀 포지셔닝; 광섬유 위치기; 군중 로봇; 경로 계획; 충돌 방지